Heterodera avenae GLAND5 Effector Interacts With Pyruvate Dehydrogenase Subunit of Plant to Promote Nematode Parasitism - Yang, Shanshan; Pan, Lingling; Chen, Yongpan; Yang, Dan; Liu, Qian; Jian, Heng (Frontiers in Microbiology, 2019)
Heterodera avenae mainly infects cereal crops and causes severe economic losses. Many studies have shown that parasitic nematodes can secrete effector proteins to suppress plant immune responses and then promote parasitism. In this study, we showed that HaGland5, a novel effector of H. avenae, was exclusively expressed in dorsal esophageal gland cell of nematode, and up-regulated in the early parasitic stage. Transgenic Arabidopsis thaliana lines expressing HaGland5 were significantly more susceptible to H. schachtii than wild-type control plants. Conversely, silencing of HaGland5 through barley stripe mosaic virus-medicated host-induced gene silencing technique substantially reduced the infection of H. avenae in wheat. Moreover, HaGland5 could suppress the plant defense responses, including the repression of plant defense-related genes, reducing deposition of cell wall callose and the burst of reactive oxygen species. Mass spectrometry, co-immunoprecipitation, and firefly luciferase complementation imaging assays confirmed that HaGland5 interacted specifically with Arabidopsis pyruvate dehydrogenase subunit (AtEMB3003).